2004
DOI: 10.1111/j.1365-2036.2004.01889.x
|View full text |Cite
|
Sign up to set email alerts
|

The risk of congenital abnormalities in children fathered by men treated with azathioprine or mercaptopurine before conception

Abstract: SUMMARYBackground: Immunosuppressive therapy with azathioprine and mercaptopurine is commonly used in patients with various chronic diseases. The few existing data on the reproductive safety of these drugs after paternal use before conception are inconclusive. Aim: To examine the risk of congenital abnormalities in children fathered by men exposed to azathioprine or mercaptopurine before conception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 23 publications
1
32
0
1
Order By: Relevance
“…Many, but not all, of the pharmacological effects of Aza are attributable to its cleavage to 6-mercaptopurine and the release of the methylnitroimidazole moiety plays an additional part in its biological activity (Calne, 1982). Aza can affect rapidly growing cells including bone marrow and gastrointestinal cells, and increase susceptibility to infection and hepatotoxicity (Norgad et al, 2004;Wu et al, 2006). Furthermore, Aza is mutagenic, genotoxic, teratogenic and several types of tumors are associated with prolonged treatment with it (Langer et al, 2003;Marcen et al, 2003;Karawya and El-Nahas, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Many, but not all, of the pharmacological effects of Aza are attributable to its cleavage to 6-mercaptopurine and the release of the methylnitroimidazole moiety plays an additional part in its biological activity (Calne, 1982). Aza can affect rapidly growing cells including bone marrow and gastrointestinal cells, and increase susceptibility to infection and hepatotoxicity (Norgad et al, 2004;Wu et al, 2006). Furthermore, Aza is mutagenic, genotoxic, teratogenic and several types of tumors are associated with prolonged treatment with it (Langer et al, 2003;Marcen et al, 2003;Karawya and El-Nahas, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 4 children with congenital abnormalities (underlying paternal diseases: glomerulonephritis and severe skin disease) were found in 54 pregnancies (7.4%) fathered by men treated with azathioprine or mercaptopurine compared with 4.1% in control pregnancies (95% CI 0.7–5.0) indicating that paternal use of azathioprine or mercaptopurine before conception might be associated with an increased risk of congenital abnormality [72] although more data are needed to determine whether the association is causal.…”
Section: Resultsmentioning
confidence: 99%
“…67 Apart from a single small study that found an increased risk of spontaneous abortions and congenital anomalies among 13 thiopurine-exposed men, 68 multiple larger studies have failed to identify an increased rate of congenital anomalies with paternal thiopurine use. [69][70][71][72] The largest prospective study of 115 pregnancies fathered by men taking thiopurines at conception found no statistically significant increase in the rate of major congenital anomalies (3.0% exposed versus 2.2% unexposed). 72 However, the rate of elective abortions was higher in the exposed group.…”
Section: Methotrexatementioning
confidence: 96%